2015
DOI: 10.1186/s13054-015-1155-7
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation (ECMO) for critically ill adults in the emergency department: history, current applications, and future directions

Abstract: Extracorporeal membrane oxygenation (ECMO) is a mode of extracorporeal life support that augments oxygenation, ventilation and/or cardiac output via cannulae connected to a circuit that pumps blood through an oxygenator and back into the patient. ECMO has been used for decades to support cardiopulmonary disease refractory to conventional therapy. While not robust, there are promising data for the use of ECMO in acute hypoxemic respiratory failure, cardiac arrest, and cardiogenic shock and the potential indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
115
1
13

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(129 citation statements)
references
References 72 publications
0
115
1
13
Order By: Relevance
“…IHCA treated with CCPR typically has a survival rate of 15%-17% and OHCA survival is even lower than 8%-10%. [15] The worst outcomes are in patients with prolonged time to ROSC. Several factors are related to the outcomes, including immediate recognition of CA, early CPR, rapid defibrillation, initial rhythm, underlying cause of CA, duration of CPR and initial resuscitation effort as well as integrated post-CA care.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…IHCA treated with CCPR typically has a survival rate of 15%-17% and OHCA survival is even lower than 8%-10%. [15] The worst outcomes are in patients with prolonged time to ROSC. Several factors are related to the outcomes, including immediate recognition of CA, early CPR, rapid defibrillation, initial rhythm, underlying cause of CA, duration of CPR and initial resuscitation effort as well as integrated post-CA care.…”
Section: Discussionmentioning
confidence: 99%
“…IHCA patients are much more likely to have witnessed CA with a shorter duration to achieve advanced cardiac life support, and with a shorter time until start of ECPR and that comorbidities are known to the treating physician implicating a bias in decision for ECMO implantation. [15] Several observational studies have found variable improvements in mortality with the use of ECPR. Haneya et al [21] compared ECPR initiated in the ED for OHCA with ECPR initiated for IHCA, and found a survival rate of 42% for IHCA patients versus only 15% for OHCA patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…El ECMO es un sistema de apoyo temporal que reemplaza la funci贸n de pulmones y coraz贸n para devolver la homeostasis a los otros 贸rganos, mientras se administra la terapia modificadora de la enfermedad o se espera la resoluci贸n del compromiso cardiorrespiratorio 1 . Estos pacientes, por lo general, tienen compromiso multisist茅mico, siendo frecuente la afectaci贸n cardiaca, pulmonar y renal concomitante.…”
Section: Definici贸nunclassified
“…, sin embargo, despu茅s de 2009, con la publicaci贸n del estudio CESAR, ha habido una expansi贸n significativa del uso de ECMO 1 . Esta investigaci贸n evidenci贸 la mejor铆a en la supervivencia en pacientes con s铆ndrome de distr茅s respiratorio agudo (SDRA) tratados con ECMO durante la pandemia de gripe H1N1.…”
unclassified